Iron-chalcogenide-based electrode materials for electrochemical energy storage. Issue 14 (25th March 2022) - Wang, Xiaojun; Wei, Qing; Li, Haichang; Sun, Jingrui; Li, Huifang; He, Yan; Liu, Zhiming
Abstract : Iron-chalcogenide-based materials are promising electrode candidates in electrochemical energy storage devices because of their high specific capacities, abundant resources, low cost and environmental friendliness. Abstract : The urgent need for clean and renewable energy has facilitated the development of advanced energy storage systems. Lithium-ion batteries (LIBs), supercapacitors (SCs) and other new energy storage technologies such as sodium-ion batteries (SIBs), potassium-ion batteries (KIBs) and lithium sulfur (Li–S) batteries meet the different requirements of high-energy density, high-power density, low cost, and large-scale energy storage, respectively. Recent research has shown that the energy storage mechanism of iron-chalcogenide-based composites endows them with high reversible specific capacities, which together with their abundant resources, low cost and environmental friendliness make them promising as electrode materials for the above-mentioned energy storage devices. This article critically and systematically reviews the research progress, synthesis strategy, storage mechanism and applications of iron-chalcogenide-based composites in LIBs, SIBs, KIBs, Li–S batteries and SCs. Meanwhile, the challenges and prospects of iron-chalcogenide-based electrode materials are also presented, which can provide beneficial guidance for the practical application of iron-chalcogenide-based composites.